Notes on the Grundrisse and the History of the Labor Process - Moraes-Neto, Benedito [UNESP] (Taylor & Francis, 2023)
The analysis of the labor process in the Grundrisse is an interesting case of the relationship between theory and history. It expresses perfectly the reality of the productive forces in today’s historical moment. Eschewing the mistaken notion that it was a portent of something that would only come to pass in the late 20th century, what is presented is a true enigma: how could an analysis of the productive reality of the mid-19th century portray the reality that ensued from a true revolution that only began in the last quarter of the 20th century? The answer should be sought in the emergence of Taylorism-Fordism, with its conceptually delayed nature, in truth, a reinvention of manufacturing system. The microelectronics revolution eliminated this mediocritizing deviation, conforming production in every segment entirely to the Grundrisse.
Keywords: labor process; machinery; microelectronics automation; Productive forces; Taylorism-Fordism